Factors Related to the Satisfaction Level of Pregnant Mothers in Antanetal Care Services Hutabayu Puskesmas, Simalungun Regency in 2022 - Siti Nurmawan (Science Midwifery, 2022)
In the era of globalization, quality in service is an indicator for achieving competitive advantage. The determining factor of customer satisfaction is the quality of the service. Universities that continue to adapt are driven by very fast global changes. (Fahmi and Dkk 2020). Service quality can be measured by comparing the perception of the expected service with the service received and felt by the patient. Patient satisfaction is the level of the patient's feelings after comparing with his expectations. If a patient is satisfied with the value provided by the product or service, he is very likely to become a customer for a long time. Indirect factors that cause high maternal and infant mortality rates include the low level of mother's knowledge and the irregular frequency of Ante Natal Care examinations. Ante Natal care is a service provided to pregnant women on a regular basis to maintain the health of the mother and baby. Quality Ante Natal Care services can increase public trust and satisfaction with health services provided by midwives and Puskesmas. Satisfaction is a human who has compared in terms of performance and also the expected results through the level of one's feelings. In another theory written by Wilton, it is stated that satisfaction or dissatisfaction is the result of the final evaluation of the customer response, namely the suitability that has been felt by the customer with the expectation that the performance of the product can be felt after the customer uses it. (Abarca 2021)